Chronic condition as a mediator between metabolic syndrome and cognition among community‐dwelling older adults: The moderating role of sex. Issue 11 (11th February 2017) - Foong, Hui Foh; Hamid, Tengku Aizan; Ibrahim, Rahimah; Haron, Sharifah Azizah; Shahar, Suzana
Abstract: Aim: Metabolic syndrome and chronic conditions are significant predictors of cognition; however, few studies have examined how they work together in predicting cognition in old age. Therefore, the present study examines whether a chronic condition mediates the association between metabolic syndrome and cognition. In addition, it discusses the moderating role of sex in the relationships between metabolic syndrome, chronic conditions and cognition. Methods: Secondary analysis was carried out of data from the Malaysian national survey that involved 2322 community residents aged 60 years or older in Peninsular Malaysia. Cognition was measured by the digit symbol substitution test. Metabolic syndrome was assessed by five biomarkers: triglyceride, fasting blood sugar, systolic blood pressure, cholesterol ratio and body mass index. Chronic conditions were assessed by self‐reported medical history. The structural equation modeling technique was used to analyze the mediation and moderation tests. Results: The number of chronic conditions partially mediated the association between metabolic syndrome and cognition. Men and women did not differ in the relationship between metabolic syndrome and cognition; however, the number of chronic conditions was found to be negatively associated with cognition in older women, but not in men. Conclusions: Metabolic syndrome might increase the likelihood of older adults to suffer from more chronic conditions; these responses might reduce their cognition. To prevent cognitive decline in old age, specific intervention to minimize the number of chronic conditions by reducing their vascular risk factors is warranted, especially among older women.Geriatr Gerontol Int 2017; 17: 1914–1920 .